Criteria of formation of readiness of future teachers of musical art to professional activity in the universities of China - Цзін, Ван (Scientific notes of the pedagogical department, 2019)
In the article the author determines the essence of the preparation of future teachers of musical art for professional activity – a process of forming motives and needs, learning knowledge, skills and abilities, development of professional and personal qualities, musical and pedagogical abilities. It was found out that the result of the preparation of future teachers of musical art for professional activity is the corresponding readiness, which we define as a stable integrative personality-professional ability of the future teacher, characterized by the presence of motivation and needs for musical and pedagogical activity, acquired knowledge, skills and abilities, provides with creative self-development, self-realization and reflection. In the structure of readiness of future teachers of musical art for professional activity, interrelated components are identified – motivational-value, cognitive, activity-procedural, personality-reflection. On the basis of the offered components, a criterial basis for measuring the levels of formation of the future readership of musical art teachers to professional activity is developed: motivational; content, procedural and reflective. The motivational criterion characterizes the level of formation of motivation and interest in the professional activity of the future teacher of musical art; value attitude of the person to this type of activity. The content criterion characterizes the level of formation of the knowledge system necessary for the future teacher of musical art. The procedural criterion measures the level of the complex application of skills and abilities that provide optimization of the educational process in the investigated aspect. Reflection criterion is measured by the formation of a future specialist as a person, his ability to professional reflection. Prospects for further scientific research we see in the justification of the pedagogical conditions for the formation of the readiness of future teachers of musical art for professional activity in higher education institutions of China and their subsequent experimental verification.